(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
this article presents some comments on the experiences of advanced foreign countries in the implementation of the protection of classified objects, as well as the advantages of the system in them, and the achievements that can be achieved by using them.